Effect of WC on the microstructure and wear resistance of Invar-WC coatings prepared by laser fusion cladding - Yuheng Li; Qiyu Gao; Xiaohu Guan; Feixiang Tian; Binbin Li; Xiaohong Zhan (Journal of Materials Research and Technology, 2025)
Invar alloys are frequently utilized in the production of composite molds, owing to their excellent dimensional stability and closely matched coefficient of thermal expansion to that of the composite materials. The inherent wear resistance of Invar alloys is limited, which significantly impacts their overall service life. Therefore, in this study, Invar-WC coating and laser remelting coating were prepared on the surface of Invar alloy by laser cladding technology. The microstructures and phase compositions of the different coatings were analyzed, and the hardness and wear resistance of the two coatings were tested and observed in the wear micro-morphology. The results show that the two coatings are well formed. The main phase composition of Invar-WC coating is Fe0.64Ni0.36, and the reinforcing phases such as W2C、M7C3, were formed in the substrate under the effect of W and C elements. The wear resistance of the remelted coating was increased by 63.55% over the substrate, and the wear resistance of the Invar-WC coating was further increased by 97.69% over the substrate. The Invar-WC coating was strengthened by fine grain reinforcement and the second phase reinforcement under the action of WC particles, which led to the increase of the hardness of the Invar-WC coating, and the enhancement of the wear-resistant property. Meanwhile, the wear mechanism of the substrate and laser remelting is characterized by adhesive wear, while the wear mechanism of the Invar-WC coating is characterized by abrasive wear due to the presence of WC particles, resulting in a significant increase in wear resistance.